2005
DOI: 10.1111/j.1365-2958.2005.04590.x
|View full text |Cite
|
Sign up to set email alerts
|

An unusual primary sigma factor in the Bacteroidetes phylum

Abstract: SummaryThe presence of housekeeping gene promoters with a unique consensus sequence in Bacteroides fragilis , previously described by Bayley et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 83 publications
0
54
0
Order By: Relevance
“…50 nucleotides upstream from the translational start codon, of IS1224, an IS21-like element (222). In Bacteroides, the consensus sequences of the two promoter regions (Ϫ33, TTTG; Ϫ7, TANNTTTG) do not conform to those of the corresponding Ϫ35 and Ϫ10 regions recognized by typical 70 factors and do not appear to require as strict a spacing (29), a situation in keeping with the existence of a particular primary sigma factor in the Bacteroidetes phylum (259). In all high-level but not in the low-level ampicillin-resistant B. fragilis strains analyzed, a TTTG sequence was present at the cepAproximal extremity of a remnant of the IS21-like element and observed with appropriate spacing with respect to the TAcc TTTG (c, nonconsensus nucleotide) region, thus contributing to the formation of a hybrid promoter (222).…”
Section: Vol 20 2007 Modulation Of Antibiotic Resistance Gene Exprementioning
confidence: 99%
“…50 nucleotides upstream from the translational start codon, of IS1224, an IS21-like element (222). In Bacteroides, the consensus sequences of the two promoter regions (Ϫ33, TTTG; Ϫ7, TANNTTTG) do not conform to those of the corresponding Ϫ35 and Ϫ10 regions recognized by typical 70 factors and do not appear to require as strict a spacing (29), a situation in keeping with the existence of a particular primary sigma factor in the Bacteroidetes phylum (259). In all high-level but not in the low-level ampicillin-resistant B. fragilis strains analyzed, a TTTG sequence was present at the cepAproximal extremity of a remnant of the IS21-like element and observed with appropriate spacing with respect to the TAcc TTTG (c, nonconsensus nucleotide) region, thus contributing to the formation of a hybrid promoter (222).…”
Section: Vol 20 2007 Modulation Of Antibiotic Resistance Gene Exprementioning
confidence: 99%
“…This primary sigma factor, ABfr , with some unique structural and functional characteristics, only recognized promoters from members of the phylum Bacteroidetes and thus explains the lack of functionality of E. coli promoters (55). Given that a similar sigma factor (72.1% identity) was also found in Flavobacterium johnsoniae (55), we believe that ABfr -like promoter sequences must also exist in members of the genus Flavobacterium.…”
mentioning
confidence: 99%
“…This is in spite of the ubiquitous distribution of members of the phylum Bacteroidetes (6, 14, 30, 31); their importance as pathogens of fish (15, 42), birds (54), and humans (7); and their roles in transforming high-molecularweight carbon compounds in soil and aquatic environments (14). Most research on gene regulation in this phylum has targeted Bacteroides (4,11,32,49,55,57) and, to a lesser extent, Porphyromonas (27,43,57,60). Early examination of the transcriptional signals in Bacteroides fragilis indicated that its promoters exhibited features distinct from those of proteobacteria (4, 55).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic tools that would make possible more thorough studies of prevotellas are still undeveloped despite their ecological and medical importance. This appears to be primarily due to the large phylogenetic distance between prevotellas and other well-characterized micro-organisms, and as a consequence of the rather specific genetic elements, exemplified by promoters, containing distinct 27/233 consensus sequences that are recognized by unusual primary s factor (Vingadassalom et al, 2005). Nevertheless, in two studies (Shoemaker et al, 1991;Accetto et al, 2005) the plasmid replicons and tetQ selectable marker derived from Prevotella and related colonic Bacteroides strains were used successfully for shuttle-vector introduction into the xylan-degrading ruminal species Prevotella bryantii, which forms a distinct phylogenetic lineage apparently somewhat closer to oral prevotellas than the other ruminal Prevotella species (Avguštin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%